MULTIPLE SHOOT REGENERATION IN DENDROBIUM FIMBRIATUM HOOK AN ORNAMENTAL ORCHID - M. F. Kabir; M. S. Rahman A. Jamal; M. Rahman; M. Khalekuzzaman (Journal of Animal and Plant Sciences, 2013)
The prime objective of the present study was to optimize and develop efficient regeneration protocol for in vitro germination, micropropagation and root induction of the orchid plant Dendrobium fimbriatum. Three investigated culture media were Phytamax (Sigma, USA; PM), Murashige and Skoog (MS) and Modified Vacin and Went (MVW) were used. Among these media PM was found to be the most effective medium for germination of orchid seedlings. In this medium, the germination rate was 100 percent. Twelve different combinations of plant growth regulators were tested for the elongation of germinated seedlings. It was revealed that MS medium fortified with 2.0 mg/l 6-benzylaminopurine (BAP) and 0.01 mg/l indole-3-butyric acid (IBA) was the most effective for shoot elongation. The average elongation rate was 4.10 cm after 30 days of culture. Sixteen different combinations of plant growth regulators were used for induction and elongation of adventitious shoots from the nodal zone of shoot explants. MS medium supplemented with 1 mg/l BAP and 0.5 mg/l Picloram was proven to be the best for multiple shoot formation and elongation. In this mediumthe average number of induced shoots per explant was 4.35. Furthermore, shortest duration (16 days) for shoot induction was recorded on this medium. Half MS medium supplemented with 1.0 mg/l indole-3-acetic acid (IAA) was found suitable for effective induction and growth of adventitious roots on the micro-propagated orchid plantlets.
Keywords: Dendrobium fimbriatum; orchid; micropropagation; callus; plant regeneration